Pelatihan Media Pembelajaran dalam Upaya Peningkatan Kreatifitas bagi Guru MI Kota Lhokseumawe - Rahmy Zulmaulida; Said Alwi; Mutia Sari; Nurul Akmal; Elfiadi; Syukran; Muhammad Iqbal (LSM Catimore dan Sahabat, 2023)
This service aims to provide training for MI teachers in Lhokseumawe City on learning media as an effort to increase creativity. This training uses the method of lectures, questions and answers and practicums. With a division of 8 JP with a duration of 50 minutes per JP. The results of this service are expected to provide contributions and suggestions for teachers in choosing creative teaching media that can be applied in the classroom, then this training is expected to contribute to the world of education, especially madrasah.